Factors affecting integration of midwifery nursing science theory with clinical practice in Vhembe District, Limpopo Province as perceived by professional midwives - Thivhulawi Malwela; Sonto M. Maputle; Rachel T. Lebese (AOSIS, 2016)
Background: Professional midwives have an important role to play in midwifery training to produce a competent midwife. According to the social learning theory, professional midwives act as role models for students. When allocated for clinical learning experiences in the training hospitals, students will have the opportunity to observe the well-trained, skilled, and experienced professional midwives. The whole process will enable students to integrate theory with practice and they will become competent. Aim: The aim of this study was to determine the factors affecting integration of midwifery nursing science theory with clinical practice as perceived by midwives. Setting: The study was conducted at the training hospitals in Vhembe district of the Limpopo Province, South Africa. These hospitals were: Donald Fraser, Siloam, and Tshidzini. Methods: A qualitative explorative, descriptive and contextual design was used. A Nonprobability, convenient sampling method was used to select 11 midwives from the following hospitals: Donald Fraser, Siloam, and Tshidzini, in Vhembe district. In-depth individual interviews were conducted. Data were analysed through open coding method. Result: One theme and five sub-themes emerged from the analysed data, namely: shortage of midwives, attitudes towards student midwives, reluctance to perform teaching functions, language barriers, and declining midwifery practice standards. Conclusion: Shortage of midwives in the clinical areas led to fewer numbers of mentors whom the students could observe and imitate to acquire clinical skills. Some of the midwives were reluctant to teach students. Recommendations were made for both training institutions and hospitals to employ preceptors for students in the clinical practical.